Laboratory characterization of firebrands involved in spot fires - Ganteaume, Anne; Guijarro, Mercedes; Jappiot, Marielle; Hernando, Carmen; Lampin-Maillet, Corinne; Pérez-Gorostiaga, Pedro; Vega, José a (Annals of Forest Science, 2011)
& Introduction Wildfires are considered the most important disturbance in the Mediterranean Basin, and some are propagated over long distances due to lift-off and ignition of firebrands. & Objectives To improve our knowledge of firebrands involved in spotting fires, flammability characteristics of eight types of firebrands commonly generated by wildfires in Southern Europe were determined under laboratory conditions. & Results All the firebrands tested showed 100% ignition frequency but with a wide range of time to ignition and flaming duration. Weight loss during combustion was exponentially related to time, and there was a decrease in the ratio of the weight at temperature T to the initial weight with increasing temperatures. In our experimental conditions, there was a significant effect of fuel moisture content on time to ignition, flaming duration, combustion and thermal decomposition. On the basis of the characteristics analysed, three firebrand groups have been identified in relation to spotting: heavy firebrands with ability to sustain flames, efficient for long-distance spotting (pine cones); light firebrands with high surface-to-volume ratio, efficient for short-distance spotting (leaves and thin barks); and light firebrands with low surface-to-volume ratio, efficient for short and, occasionally, long-distance spotting (all the other types of firebands).
Keywords: ember; Fire behaviour; firebrand; flammability parameters; Wildfire